THE IMPORTANCE OF GLYCATED HEMOGLOBIN IN THE DIAGNOSIS OF DIABETES - Allayorov Abbos Dustmuhammedovich; Dustqulova Yulduzkhon Mahamat kizi (TADQIQOTLAR, 2025)
Abstract: Glycated hemoglobin (HbA1c) plays a key role in the diagnosis of diabetes, as it allows you to assess the average blood glucose level over the past three months. This makes it a more reliable indicator than a regular blood glucose test, which can fluctuate depending on a number of factors such as stress, physical activity, and time of day.The determination of HbA1c concentration is a simple and convenient method  that  allows  doctors  to  quickly  establish  a  diagnosis  and  begin  appropriate treatment. The HbA1c level not only indicates the presence of diabetes, but also allows us to evaluate the effectiveness of the current therapeutic strategy, which significantly affects long-term treatment planning.